Polymer planar Bragg grating for sensing applications - Rosenberger, Manuel; Hartlaub, N.; Koller, G.; Belle, S.; Schmauß, Bernhard; Hellmann, R. (SPIE Optics and Optoelectronics Conference, 2013)
Bragg gratings have become indispensable as optical sensing elements and are already used for a variety of technical applications. Mainly silica fiber Bragg gratings (FBGs) have been extensively studied over the last decades and are nowadays commercially available. Bragg grating sensors consisting of other materials like polymers, however, have only recently come into the focus of fundamental and applied research. Polymers exhibit significantly different properties advantageous for many sensing applications and therefore provide a good alternative to silica based devices. In addition, polymer materials are inexpensive, simple to handle as well as available in various forms like liquid resists or bulk material. Accordingly, polymer integrated optics attract increasing interest and can serve as a substitute for optical fibers.We report on the fabrication of a planar Bragg grating sensor in bulk Polymethylmethacrylate (PMMA). The sensor consists of an optical waveguide and a Bragg grating, both written simultaneously into a PMMA chip by a single writing step, for which a phase mask covered by an amplitude mask is placed on top of the PMMA and exposed to the UV radiation of a KrF excimer laser. Depending on the phase mask period, different Bragg gratings reflecting in the telecommunication wavelength range are fabricated and characterized. Reflection and transmission measurements show a narrow reflection band and a high reflectivity of the polymer planar Bragg grating (PPBG). After connecting to a single mode fiber, the portable PPBG based sensor was evaluated for different measurands like humidity and strain. The sensor performance was compared to already existing sensing systems. Due to the obtained results as well as the rapid and cheap fabrication of the sensor chip, the PPBG qualifies for a low cost sensing element. © (2013) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use onl
lhft_intern.bib::Rosenberger2013a